Answer:
b= -8
Step-by-step explanation:
we have: 3y +12 = 6x <=> y + 4 = 2x <=> y= 2x - 4
=> 2y=4x + b
<=> 2(2x-4) = 4x +b
<=> 4x - 8= 4x +b
<=> b = -8
Answer:
Give the person above me brainliest
Step-by-step explanation:
Answer:
] y=x-4
-2x+y=18
y - x = -4
y - 2x = 18
equation [2] for the variable y
[2] y = 2x + 18
// Plug this in for variable y in equation [1]
[1] (2x+18) - x = -4
[1] x = -22
// Solve equation [1] for the variable x
[1] x = - 22
// By now we know this much :
y = 2x+18
x = -22
// Use the x value to solve for y
y = 2(-22)+18 = -26
Step-by-step explanation:
please mark me as brainlist please